Age-associated changes in oxidative damage and the activity of antioxidant enzymes in rats with inherited overgeneration of free radicals - Sinitsyna, Olga (John Wiley & Sons, Ltd, 2006)
Reactive oxygen species have been hypothesized to play an important role in the process of aging. To investigate the correlation between oxidative stress and accumulation of protein and DNA damage, we have compared the age-dependent levels of protein carbonyl groups and the activities of antioxidant enzymes superoxide dismutase, catalase and glutathione peroxidase in cytosol and mitochondrial extracts from liver cells of Wistar and OXYS rats. The latter strain is characterized by increased sensitivity to free radicals. Faster age-dependent increase in the level of protein carbonyl groups was found in OXYS as compared with Wistar rats. A complicated enzyme-specific pattern of age-dependent changes in the activities of antioxidant enzymes was observed. Long-term uptake of dietary supplements Mirtilene forte (extract from the fruits of Vaccinium myrtillus L.) or Adrusen zinco (vitamin E complex with zinc, copper, selenium and ω-3 polyunsaturated fatty acids) sharply decreased the level of protein oxidation in cytosol and mitochondrial extracts of hepatocytes of Wistar and of OXYS rats. Both dietary supplements increased the activity of catalase in the liver mitochondria of OXYS rats. Our results are in agreement with the shorter life-span of OXYS and with the mitochondrial theory of aging, which postulates that accumulation of DNA and protein lesions leads to mitochondrial dysfunction and accelerates the process of aging.